2013
DOI: 10.1038/srep02458
|View full text |Cite
|
Sign up to set email alerts
|

Effectively control negative thermal expansion of single-phase ferroelectrics of PbTiO3-(Bi,La)FeO3 over a giant range

Abstract: Control of negative thermal expansion is a fundamentally interesting topic in the negative thermal expansion materials in order for the future applications. However, it is a challenge to control the negative thermal expansion in individual pure materials over a large scale. Here, we report an effective way to control the coefficient of thermal expansion from a giant negative to a near zero thermal expansion by means of adjusting the spontaneous volume ferroelectrostriction (SVFS) in the system of PbTiO3-(Bi,La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
87
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 97 publications
(89 citation statements)
references
References 40 publications
1
87
1
Order By: Relevance
“…In order to maintain the thermal stability and physical properties, a universal and effective method to tailor the thermal expansion of metal or semimetal is strongly expected. So far, doping method to change the chemical composition is regarded as the most common way 2, 3, 4. The most famous example is invar alloy,5, 6 showing a low coefficient of thermal expansion (CTE) during magnetic transition.…”
mentioning
confidence: 99%
“…In order to maintain the thermal stability and physical properties, a universal and effective method to tailor the thermal expansion of metal or semimetal is strongly expected. So far, doping method to change the chemical composition is regarded as the most common way 2, 3, 4. The most famous example is invar alloy,5, 6 showing a low coefficient of thermal expansion (CTE) during magnetic transition.…”
mentioning
confidence: 99%
“…Since most materials expand on heating and contract on cooling, materials with opposite property, namely negative thermal expansion (NTE), are particularly desired for tailoring CTEs. The rediscovery of NTE in ZrW 2 O 8 in a wide temperature range (Evans et al, 1996, 1997a) triggered continuous efforts on understanding the NTE phenomenon and searching for more NTE materials (Yang et al, 2007; Chen et al, 2013, 2015; Tallentire et al, 2013; Lama et al, 2014; Liu et al, 2014; Peng et al, 2014; Xiao et al, 2014; Hu et al, 2015). To date, different families of NTE materials based on various mechanisms, such as the phonon effect (Pryde et al, 1996; Wang et al, 2011; Bridges et al, 2014; Cheng et al, 2016a; Ge et al, 2016a), magnetovolume effect (Takenaka and Takagi, 2005; Qu et al, 2012; Yan et al, 2014), spontaneous ferroelectric polarization (Chen et al, 2013; Peng et al, 2016), and charge transfer (Long et al, 2009; Azuma et al, 2011; Yamada et al, 2016) have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The rediscovery of NTE in ZrW 2 O 8 in a wide temperature range (Evans et al, 1996, 1997a) triggered continuous efforts on understanding the NTE phenomenon and searching for more NTE materials (Yang et al, 2007; Chen et al, 2013, 2015; Tallentire et al, 2013; Lama et al, 2014; Liu et al, 2014; Peng et al, 2014; Xiao et al, 2014; Hu et al, 2015). To date, different families of NTE materials based on various mechanisms, such as the phonon effect (Pryde et al, 1996; Wang et al, 2011; Bridges et al, 2014; Cheng et al, 2016a; Ge et al, 2016a), magnetovolume effect (Takenaka and Takagi, 2005; Qu et al, 2012; Yan et al, 2014), spontaneous ferroelectric polarization (Chen et al, 2013; Peng et al, 2016), and charge transfer (Long et al, 2009; Azuma et al, 2011; Yamada et al, 2016) have been reported. Among the materials, the family of A 2 M 3 O 12 (A = transition metal or a mixture of tetravalent and bivalent cations, M = W, Mo) have been particularly attractive, because whose NTEs go over a wide temperature range and can be tuned from low positive to large negative values due to chemical flexibility (Evans et al, 1997b; Suzuki and Omote, 2006; Wu et al, 2009, 2012, 2014; Li et al, 2011; Das et al, 2013; Miller et al, 2013; Song et al, 2014a; Liu et al, 2015; Chen et al, 2016; Cheng et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…M = W, Mo)151617181920 and ZrV 2 O 7 2122, cyanides M(CN) 2 (M = Zn, Cd) and Ag 3 [Co(CN) 6 ]2324, fluorides ScF 3 and ZnF 2 2526, anti-perovskite manganese nitrides Mn 3 AN (A = Zn, Ga and Ge, etc. )272829303132, perovskite structure PbTiO 3 33, BiNiO 3 34 and LaCu 3 Fe 4 O 12 35, and high quartz structure beta-Li 2 Al 2 SiO 6 36, beta-LiAlSiO 4 37, and keatite38, etc. The NTE mechanisms in the open framework structure arise mainly from phonon anharmonicity361121232425 while in others most related to phase transition, such as magnetovolume effect in anti-perovskite manganese nitrides, ferroelectric-to-paraelectric phase transition in PbTiO 3 and temperature-induced intersite charge transfer in LaCu 3 Fe 4 O 12 and BiNiO 3 .…”
mentioning
confidence: 99%